Influence of Legislation on Road Traffic Safety - Rajsman, Marijan; Lisicin, Georg-Davor (Promet - Traffic&Transportation, 2012)
The objective of this paper is to analyse road traffic safety in the Republic of Croatia based on the selected indicators which were used by the legislator in bringing the Law on Road Traffic Safety which has been in force since 28 July 2004, and the achieved effects in reaching the desired safety level in the three-year period from 2005 to 2007. The aim of the research is to establish a prognostic trend of the values of the studied indicators in the time period following the enforcement of new legal regulations. Adequate safety indicator values for the respective period were analyzed using the methods of analysis and synthesis, mathematical statistics as well as trend assessment based on the found mathematical prognostic models. Based on the results of this research it was found that the basic hypothesis according to which the implementation of new legal guidelines had to result in positive change in the condition of road traffic safety, failed to be confirmed. A change in the road traffic safety improvement strategy has been proposed as well as a more significant participation and recognition of the profession and science in this field which is of great significance for the society. KEY WORDS: influence of legal regulations, road traffic safety, effects and tendencies